2019
DOI: 10.2147/rru.s220219
|View full text |Cite
|
Sign up to set email alerts
|

<p>An Ergonomic Assessment Of Four Different Donor Nephrectomy Approaches For The Surgeons And Their Assistants</p>

Abstract: IntroductionOpen surgery is increasingly being replaced by laparoscopic approaches that are more demanding for the surgical team. The physical and mental workload of these approaches have not been quantified.Materials and methodsA multicenter prospective study was performed evaluating the physical and mental stresses of 4 surgical approaches (open surgery [OS], standard laparoscopy [SL], hand-assisted laparoscopy [HAL], and robot-assisted laparoscopy [RAL]) for donor nephrectomy for the surgeon and their assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Mental demand was mostly measured by subjective measures such as self‐report questionnaires, most commonly the NASA‐TLX [7, 15, 18, 20, 27, 30, 31]. These studies all showed no differences in mental demand between the surgical techniques except for in young surgeons [27] and one study showing less mental demand in RS than LS [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental demand was mostly measured by subjective measures such as self‐report questionnaires, most commonly the NASA‐TLX [7, 15, 18, 20, 27, 30, 31]. These studies all showed no differences in mental demand between the surgical techniques except for in young surgeons [27] and one study showing less mental demand in RS than LS [20].…”
Section: Resultsmentioning
confidence: 99%
“…Among these studies, eight studies favoured RS [4,[14][15][16][17][18][19][20], one study showed a trend towards favouring RS [21], and one study favoured RS over LS but showed no difference to OS [22]. Most studies (N = 10) showed mixed results [7,[23][24][25][26][27][28][29][30][31] with only three studies showing no difference between the surgical modalities [32][33][34], and one study with inconclusive results [35].…”
Section: Study Findingsmentioning
confidence: 99%
“…NASA-TLX is a widely used technique for workload measurement in aviation, military and healthcare. NASA-TLX can be found in traditional MIS mental workload estimation [ 48 , 49 , 50 , 51 , 52 ], and employed in the case of surgical robotics workload assessment as well [ 8 , 32 , 34 , 40 , 41 , 43 , 45 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. There are additional mental workload assessment techniques that are not originally created for surgery, and used in workload assessment for RAMIS.…”
Section: Technical Approaches For Non-technical Skill and Mental Workload Assessment In Ramismentioning
confidence: 99%
“…With self-rating tools, the real stressors of the surgery can be observed, and other approaches have to fit to the clinical relevance. Self-rating studies can be found in Table 5 under the following references: [ 30 , 31 , 32 , 34 , 40 , 41 , 42 , 43 , 44 , 50 , 56 , 57 , 59 , 60 , 61 , 62 , 63 , 64 , 66 , 68 , 69 , 70 , 71 , 72 , 75 , 76 , 81 , 85 , 93 , 94 , 95 ].…”
Section: Technical Approaches For Non-technical Skill and Mental Workload Assessment In Ramismentioning
confidence: 99%
“… 2 4 The da Vinci Surgical System (Intuitive Surgical, Mountain View, CA) and subsequent introduction of robot-assisted DN (RADN) in 2002 5 has offered surgeons a safe alternative to LDN with improved surgical vision and ergonomic relief. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%